INVESTMENT FEASIBILITY ANALYSIS, STORAGE CAPACITY, SENSITIVITY ANALYSIS. - ARIFIAN ADIN (NIM : 13412018), MUHAMMAD
Liquified petroleum gas (LPG) has become an essential need of every Indonesian household. As a state-owned corporation (BUMN), PT Pertamina is mandated to efficiently manage and distribute LPG in Indonesia while also ensuring its viability and affordability. In running its operation in West Java, PT Pertamina has been reliant on the service of a private depot (LPG storage facility) in Eretan to cover the insufficient capacity, which has been inflating its operation cost and reducing its spending efficiency. Therefore, PT Pertamina is planning to invest in a project to increase the storage capacity of Depot Balongan in order to minimize its reliant on Depot Eretan and cut cost. However, a feasibility analysis must first be conducted to determine if the investment will be feasible to run or vice versa. Feasibility analysis will assess four aspects of the investment, which are the marketing aspect, the legal and environmental aspect, the technical aspect, and the financial aspect. Market aspect feasibility will be determined by estimating the potential revenue from investing and the suitability of market size. Legal and nvironmetal aspect feasibility will be determined by the complience of company to regulations related to the project. Technical aspect feasibility will be determined by the capability of the company to provide all the technical requirements neccessary for running investment. Parameters for financial feasibility, within this research, includes net present value (NPV), internal rate of return (IRR), payback period (PBP), discounted payback period (DPBP), break even point (BEP), and cash flow. The result of the feasibility study showed that the investment to increase the storage capacity of Depot Balongan is feasible from all across marketing aspect, legal and environmental aspect, and technical aspect. Furthermore, calculation and analysis on the financial feasibility parameters showed that the investment possesses NPV of Rp 460.679.859.550, IRR of 31,03 %, PBP & DPBP of over 4,18 years and 5,49 consecutively, BEP at maximum on 66% of revenue, and a positive cash flow all through the investment period. Feasibility analysis on all four aspects concludes that the investment is feasible to run. Furthermore, sensitivity analysis conducted on the investment also showed that its feasibility will be highly influenced by sudden changes of value in LPG operation cost and USD currency.